Using Facebook as a teaching and learning tool for class project - Dzuratul Ain binte Cik Mit, * (Sunway College Kuala Lumpur, 2015)
The idea of using social media such as Facebook, Twitter, Google+ and other social networking sites for teaching and learning might not be appealing to many educators. The detrimental effects that social networking sites might have on the students are some of the concerns raised by these educators, involving the invasion and exploitation of privacy, inappropriate media communication or content, distraction from the traditional way of learning, and many more. However, if the proper structure is put in place and the content is monitored, such social media can become a valuable and interactive teaching and learning tool. In this paper, the author will share some strategies used on Facebook specifically for class projects, due to its use as a communication platform for online discussions and a way for educators to connect with the students.